Accuracy of diagnostic content of hospital activity analysis in infectious diseases. Issue 6174 (19th May 1979) - George, A M; Maddocks, G B
Abstract : Hospital activity analysis (HAA) was used to identify 2151 patients in whom the diagnostic code fell within the infectious disease categories of the International Classification of Disease. The clinical notes of these patients were examined by a doctor and in 414 (19.2%) the diagnostic coding was incorrect. Diarrhoea and viral infections were miscoded most often. The possibility of inaccuracy must be considered when HAA aggregated data are used for planning purposes. Accuracy could be improved if clinicians routinely completed the diagnostic sections of the HAA form.